The mediating role of nutrition knowledge level in the effect of mindfulness on healthy nutrition obsession - Kurtipek, Serkan; Güngör, Nuri Berk; Esentürk, Oğuz Kaan; Tolukan, Ersan (Progress in Nutrition, 2020)
Study Objectives: The study aimed to determine the mediating role of nutritional knowledge level in the effect of mindfulness of individuals, who receive sports education at the undergraduate level, on the healthy nutrition obsession. Methods: The sample of the study consists of 339 participants, 163 of which are female and 176 are male, who continue their education in a higher education institution, which provides undergraduate sports education, in Ankara province in the 2019-2020 academic year. “Mindfulness Scale”, the “Orto-11 (Healthy Nutrition Obsession) Scale” and “Nutrition Knowledge Level for Adults Scale” were used as data collection tools. In addition to descriptive statistics, structural correlation models aimed at testing the Pearson Correlation and the constructed theoretical model were used in the analysis of the data. Results: The mean score obtained by the participants was determined as (x̄=3.76) for the Mindfulness Scale, as (x̄=2.20) for the Healthy Nutrition Obsession Scale, and as (x̄=2.31) for the Adult Nutrition Knowledge Level Scale. A statistically significant effect was found in the relationship of mindfulness with a healthy nutrition obsession (β1=.16; p